STUDI OBSERVASI PERKEMBANGAN SOSIAL-EMOSIONAL ANAK USIA DINI DAN IMPLIKASINYA TERHADAP PENDIDIKAN LUAR SEKOLAH - Adela Anita; Asri Cahyanengdian (IKIP Siliwangi, 2026)
This study aims to analyze the social-emotional development of early childhood and examine its implications for non-formal education. The study employed a qualitative approach with a descriptive research design. The research was conducted at TK Pertiwi Merauke, involving children aged 3–6 years selected through purposive sampling. Data were collected through observation, documentation, and field notes, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that children's social-emotional development varies according to their age levels. Children aged 3–4 years tend to exhibit egocentric behavior, children aged 4–5 years begin to develop social interaction skills, while children aged 5–6 years demonstrate more mature abilities in empathy, cooperation, and emotional regulation. The development is influenced by several factors, including family environment, teacher roles, and peer interaction. The study reveals that non-formal education plays a strategic role in strengthening children's social-emotional development through contextual and continuous learning experiences within family and community environments. However, the integration between formal education and non-formal education is not yet optimal. Therefore, a holistic educational approach is needed through collaboration among schools, families, and communities to support optimal social-emotional development in early childhood.